2020
DOI: 10.1155/2020/1716084
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Fairness Concern and Different Business Objectives on the Complexity of Dual-Channel Value Chains

Abstract: is paper considers a Stackelberg game model in a dual-channel supply chain, which is composed of a manufacturer and a retailer. e manufacturer and retailer consider fairness concern in the market competition, and the manufacturer takes market share and profit as his/her business objectives. e entropy complexity and dynamic characteristic of the dual-channel system are analyzed through mathematical analysis and numerical simulation, such as local stability, bifurcation, entropy, and chaos. e results show that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Therefore it is widely used in general discrete dynamic systems. Based on this, the dynamic system with new controllers is established as follows [ 24 ]: …”
Section: Chaos Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is widely used in general discrete dynamic systems. Based on this, the dynamic system with new controllers is established as follows [ 24 ]: …”
Section: Chaos Controlmentioning
confidence: 99%
“…Systematic bifurcations with variation of the adjustment parameter u Systematic bifurcations with variation of adjustment parameter u used in general discrete dynamic systems. Based on this, the dynamic system with new controllers is established as follows[24]:…”
mentioning
confidence: 99%
“…For the system disturbed by weak noise, its variation can be seen as the random factors around the deterministic system and transformation between them [33]. When interference factors are very small, the motion state of the system would not be affected by the disturbance term; when interference factors are very large, the state of the system would be changed.…”
Section: Equilibrium Points Conditions For Existence and Local Stabmentioning
confidence: 99%
“…Xin and Sun [32] studied a differential oligopoly game in which a production-planning single-decision problem is extended to a production-planning and water-saving dualdecision problem, and the decisions are affected simultaneously by both the product and the water right prices. Li et al [33] studied a Stackelberg game model in a dualchannel supply chain, in which the manufacturer and retailer all considered fairness concern in the price game. Li et al [34] constructed a dual-channel valued chain in which the manufacturer made green innovation input and the retailer provided channel service, and they make the dynamic price game in decentralized and centralized decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they simplified the utility function of fairness concern. Li et al [21] researched the influence of different business objectives and fairness concern on the complexity of dual-channel value chains and the research found that the manufacturer and the retailer with the high level of fairness concern are always bad for the leading manufacturer but not always unfavorable to the follower retailer. Zhen et al [40] developed a supply chain that included a manufacturer producing and selling products through direct online channel and a retailer sells directly to consumers through online and offline channels.…”
mentioning
confidence: 99%